Malaria and determinants of health: a scoping review of Malaria vulnerabilities in Southeast Asia - Md Hanif, Shahrul Azhar; Hassan, Mohd Rohaizat; Safian, Nazarudin; Sutan, Rosnah; Alabed, Alabed Ali A.; Rafi’i, Muhammad Ridzwan; Md Asari, Siti Najiha; Naserrudin, Nurul Athirah; Dapari, Rahmat (BioMed Central, 2025)
Introduction: Malaria continues to pose a considerable public health challenge in Southeast Asia, necessitating control efforts that consider region-specific vulnerabilities. Although global risk factors are well-documented, the interplay of social determinants of health in shaping malaria vulnerability within SEA populations is less thoroughly explored. Objective: This scoping review aims to determine elements influencing vulnerabilities towards malaria in SEA populations. In addition, this study seeks to explore how various social determinants of health contribute to the increased malaria vulnerabilities in this region. Method: This review adhered to the PRISMA-ScR guidelines. A systematic literature search was performed in PubMed, Scopus, and Web of Science from October to November 2024, focusing on peer-reviewed, open-access quantitative studies published from 2014 to 2024. Studies that addressed the risk or vulnerability of malaria in SEA populations were included. Multiple reviewers independently conducted screening, data charting, and thematic synthesis. Result: Twenty-two studies met the inclusion criteria, encompassing various malaria-endemic settings in SEA, including cross-border regions and migrant populations. The findings were synthesized using a social determinants of health lens, resulting in five thematic domains: biological influences, demographic and socioeconomic parameters, built and lived environments, behaviour and practices, and access to healthcare services and information. Conclusion: The vulnerability of SEA population to malaria is multifaceted and deeply entrenched in a web of complex, interrelated factors. Effective control requires region-specific, multi-sectoral strategies that address these vulnerabilities through targeted interventions, strengthened health systems, and equitable public health policies.